AMIA Board White Paper: AMIA 2017 core competencies for applied health informatics education at the master's degree level. (26th October 2018) - Valenta, Annette L; Berner, Eta S; Boren, Suzanne A; Deckard, Gloria J; Eldredge, Christina; Fridsma, Douglas B; Gadd, Cynthia; Gong, Yang; Johnson, Todd; Jones, Josette; Manos, E LaVerne; Phillips, Kirk T; et al.
Abstract: This White Paper presents the foundational domains with examples of key aspects of competencies (knowledge, skills, and attitudes) that are intended for curriculum development and accreditation quality assessment for graduate (master's level) education in applied health informatics. Through a deliberative process, the AMIA Accreditation Committee refined the work of a task force of the Health Informatics Accreditation Council, establishing 10 foundational domains with accompanying example statements of knowledge, skills, and attitudes that are components of competencies by which graduates from applied health informatics programs can be assessed for competence at the time of graduation. The AMIA Accreditation Committee developed the domains for application across all the subdisciplines represented by AMIA, ranging from translational bioinformatics to clinical and public health informatics, spanning the spectrum from molecular to population levels of health and biomedicine. This document will be periodically updated, as part of the responsibility of the AMIA Accreditation Committee, through continued study, education, and surveys of market trends.